Aqueous humor cytokines levels and illuminated microcatheter-assisted circumferential trabeculotomy outcome in open-angle glaucoma patients: a 24-month prospective study - Wu, Tingyi; Ji, Qianqian; Liao, Yanfeng; Zhao, Xiaoyu; Hong, Ying (Frontiers in Immunology, 2025)
PurposeTo investigate the influence of aqueous humor cytokines levels on the failure of illuminated microcatheter-assisted circumferential trabeculotomy (MAT) in open-angle glaucoma (OAG) patients.MethodsThis was a prospective case series with a follow-up period of 24 months. General information and ocular examinations were recorded. Aqueous humor was collected at the time of surgery. Eight aqueous humor cytokines were analyzed: CCL2, VCAM-1, ICAM-1, IL-6, IL-8, IL-10, CXCL10 and G-CSF. Bioinformatics analysis was used to explore the protein network and the possible pathways related to OAG. Surgical failure was defined as a requirement for glaucoma reoperation or intraocular pressure (IOP) greater than 21mmHg with more than 3 topical antiglaucoma medications at 24-month follow-up.ResultsSixty-five eyes were enrolled (58 success and 7 failure). The levels of CCL2, ICAM-1, IL-6 and CXCL10 in aqueous humor were significantly higher in the surgical failure group (P = 0.024, 0.002, 0.022 and 0.008, respectively). A higher percentage of secondary glaucoma (P < 0.001), younger age (P = 0.019), worse preoperative BCVA (P = 0.022), higher preoperative IOP (P = 0.022) and more preoperative topical antiglaucoma medications (P = 0.029) were significantly observed in the surgical failure group. Bioinformatics analysis identified 4 hub proteins, including CCL2, CXCL10, IL-6 and CXCR3, and demonstrated the potential role of chemokine signaling pathway in MAT surgical outcome.ConclusionHigher concentrations of CCL2, ICAM-1, IL-6 and CXCL10 in the aqueous humor were related to the failure of MAT surgery in OAG patients, and chemokine signaling pathway might be associated with the surgical outcome.